2017
DOI: 10.1063/1.4979722
|View full text |Cite
|
Sign up to set email alerts
|

On the c-Si/SiO2 interface recombination parameters from photo-conductance decay measurements

Abstract: The recombination of electric charge carriers at semiconductor surfaces continues to be a limiting factor in achieving high performance optoelectronic devices, including solar cells, laser diodes, and photodetectors. The theoretical model and a solution algorithm for surface recombination have been previously reported. However, their successful application to experimental data for a wide range of both minority excess carrier concentrations and dielectric fixed charge densities has not previously been shown. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 74 publications
(109 reference statements)
5
36
0
Order By: Relevance
“…In n‐type silicon, where passivation is more effective, Larionova et al demonstrated a S eff of 0.42 cm s −1 , and Bonilla et al obtained 0.17 cm s −1 , for 2.5 and 1 Ωcm resitivities, respectively. They reported that the mechanisms involved in such good passivation were a combination of the intrinsic field‐effect due to grown‐in charge in the nitride layer, the extrinsic chemical passivation of the Si–SiO 2 interface (due to hydrogen ingress during PECVD deposition of the nitride), and the subsequent addition of extrinsic field‐effect via corona discharge . When used on a textured surface, Bonilla et al reported a S eff of 34 cm s −1 in an as deposited oxide‐nitride stack, and 14 cm s −1 after extrinsic addition of charge.…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 99%
“…In n‐type silicon, where passivation is more effective, Larionova et al demonstrated a S eff of 0.42 cm s −1 , and Bonilla et al obtained 0.17 cm s −1 , for 2.5 and 1 Ωcm resitivities, respectively. They reported that the mechanisms involved in such good passivation were a combination of the intrinsic field‐effect due to grown‐in charge in the nitride layer, the extrinsic chemical passivation of the Si–SiO 2 interface (due to hydrogen ingress during PECVD deposition of the nitride), and the subsequent addition of extrinsic field‐effect via corona discharge . When used on a textured surface, Bonilla et al reported a S eff of 34 cm s −1 in an as deposited oxide‐nitride stack, and 14 cm s −1 after extrinsic addition of charge.…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 99%
“…A reduction in Q IL,eff could be caused by the injection of charge carriers from the silicon into the IL stack which is possible with the O/N IL stack under applied voltage conditions as discussed above (section 4.2) and which might happen under illumination as well . Furthermore, when the interface defect density is of the same order as the fixed charge density, the charge associated with interface defects could reduce the effectiveness of the field‐effect passivation …”
Section: Resultsmentioning
confidence: 99%
“…This will be explored in detail in Section IV. The resulting interface charge ranges from 1.5 to 2.8 × 10 12 q/cm 2 , which includes values of dielectric charge necessary for highquality FEP as modelled in [40]. The effective lifetimes produced with these quantities of ionic interface charge are all similar, despite an increase in FEP caused by the increasing interface charge.…”
Section: A Ion Deposition By Thermal Evaporationmentioning
confidence: 99%